2005
DOI: 10.1017/s0012162205000034
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative incidence of childhood autism: a total population study of better accuracy and precision

Abstract: Most studies on the frequency of autism have had methodological problems. Most notable of these have been differences in diagnostic criteria between studies, degree of cases overlooked by the initial screening, and type of measurement. This study aimed to replicate the first report on childhood autism to address cumulative incidence as well as prevalence, as defined in the International Statistical Classification of Diseases and Related Health Problems, 10th revision (ICD-10) Diagnostic Criteria for Research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 35 publications
8
62
1
4
Order By: Relevance
“…The gender ratios of both the probands and the infants with ASD outcomes in this study were similar to those reported in the general ASD population. 27,28 If multiplex families were overrepresented in the current sample, this could elevate recurrence rates, but this was not the case. The current sample was 6% multiplex (before the birth of the infant), whereas other studies report multiplex rates of approximately 10%.…”
Section: Discussionmentioning
confidence: 86%
“…The gender ratios of both the probands and the infants with ASD outcomes in this study were similar to those reported in the general ASD population. 27,28 If multiplex families were overrepresented in the current sample, this could elevate recurrence rates, but this was not the case. The current sample was 6% multiplex (before the birth of the infant), whereas other studies report multiplex rates of approximately 10%.…”
Section: Discussionmentioning
confidence: 86%
“…The disorder is more common than previously supposed, with a worldwide frequency of >0.6% (Honda et al, 2005;Baird et al, 2006;Williams et al, 2006). The region with the maximum reported rate (3% of births)…”
Section: Introductionmentioning
confidence: 87%
“…Incidence rates, despite their theoretical advantages for studying risk, are of more limited utility in autism epidemiology because not only is autism diagnosis distal to disease initiation but also time between initiation and diagnosis is likely influenced by a wide range of other factors potentially unrelated to risk. Cumulative incidence, however, may be informative for descriptive epidemiologic studies of birth cohorts (64). Many population-based prevalence surveys of autism have been conducted since the 1960s with a number of recent reviews summarizing these surveys and evaluating changes in reported estimates over time (48,78,178).…”
Section: Descriptive Epidemiology Prevalencementioning
confidence: 99%